2012
DOI: 10.4103/0019-5154.97665
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of pediatric dermatoses in a tertiary care centre of South West Rajasthan

Abstract: Background:The evaluation for skin disorders forms an important component of primary health care practice for all including children. The prevalence of certain skin diseases in children can reflect status of health, hygiene, and personal cleanliness of a community.Aims:This study was planned to evaluate the magnitude of skin diseases, pattern of various dermatoses, factors contributing to these dermatoses and concurrent systemic disease among children up to five years of age.Materials and Methods:Consecutive 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
25
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 12 publications
3
25
0
Order By: Relevance
“…The most common diagnosis was infections and infestations (n=116, 51.3%) followed by dermatitis (n=63, 27.8%); which was also found in other studies. 6,16,18 Impetigo (n=25, 11%) was found to be the commonest among the infectious cause as in other studies. 6,11,13,16,[18][19] Memon et al found scabies to be the commonest amongst the infectious disease (45.5%).…”
Section: Discussionmentioning
confidence: 48%
See 2 more Smart Citations
“…The most common diagnosis was infections and infestations (n=116, 51.3%) followed by dermatitis (n=63, 27.8%); which was also found in other studies. 6,16,18 Impetigo (n=25, 11%) was found to be the commonest among the infectious cause as in other studies. 6,11,13,16,[18][19] Memon et al found scabies to be the commonest amongst the infectious disease (45.5%).…”
Section: Discussionmentioning
confidence: 48%
“…6,16,18 Impetigo (n=25, 11%) was found to be the commonest among the infectious cause as in other studies. 6,11,13,16,[18][19] Memon et al found scabies to be the commonest amongst the infectious disease (45.5%). 17 However in our study scabies was seen in (n=22) 9.6% cases only.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…In their study, Dogra and Kumar[ 23 ] found only 11.4% of disorders of infectious etiology; however, various other authors in India have reported that disorders of infectious and infestations etiology contributed to 35.6% to 85.2%. [ 24 25 26 27 ]…”
Section: Discussionmentioning
confidence: 99%
“…The western part of Rajasthan, have a great amount of the Mycoses infections. In Jodhpur, the Sun City has been evaluated for the presence of dermatophytoses in the ruler hospital "Mathuradas Mathur Hospital" [142]. In South east part of Rajasthan, Kota districts have an atmospheric humid climate which is suitable for overgrowth of dermatophytes.…”
Section: Ecological Status Of Dermatophytesmentioning
confidence: 99%